The Role of Curcumin in Preventing Naturally Occurring Leiomyoma in the Galline Model - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Ozercan, Ibrahim H.; Kabil, Nashwa; Ozpolat, Bulent (Mdpi, 2024)
Background: Leiomyoma (LM) is the most commonly identified tumor in the genital tract, occurring in 70-80% of women. The only treatment option is surgery, which significantly influences healthcare costs and negatively influences women's survival and reproductive capacity. Therefore, identifying safe and effective chemopreventive and treatment modalities is needed. Methods: We investigated the effects of 12 months of daily curcumin (0, 25.8, and 53 mg/kg) diet on the incidence and growth of spontaneously developing LM tumors in a galline (hen) model. Results: LM tumors were detected in 58.9% (53/90) of the control hens as spontaneous occurrences, while they were observed in 37.7% (34/90) and 24.5% (22/90) of hens treated with daily doses of 25.8 mg or 53.0 mg, respectively, over 12 months. This reduced LM development by 35% and 58.5%, respectively (p = 0.004). We also observed a dose-dependent inhibition of LM-tumor growth and NF-kappa B, mTOR, p70S6K1, and 4E-BP1 signaling while inducing Nrf2/HO1 pathway induction LM tumors collected from hens fed with curcumin (p < 0.05). Curcumin intake notably reduced levels of TGF-beta 1, alpha-SMA, and collagen type 1, with dose-dependent effects (p < 0.001). Conclusions: The findings suggest that daily curcumin consumption significantly reduces the incidence of naturally occurring LMs and suppresses tumor growth. This indicates that regular curcumin intake may be an effective preventive measure against LMs.
Keywords: curcumin; prevention; spontaneous leiomyoma; laying hen